Current practices and perceptions among clinicians in osteoarthritis and osteoporosis management in Indian settings - S., Manjula; M., Krishna Kumar (International Journal of Research in Orthopaedics, 2025)
Background: Although there were several clinical studies available, there was a dearth of studies among clinicians in actual practice. So, the present study aimed to assess clinician perspectives on the prevalence, risk factors, diagnosis and management practices of osteoarthritis (OA) and osteoporosis (OP) in routine clinical settings, to identify gaps in awareness, treatment approaches and patient compliance. Methods: The cross-sectional study utilized a 23-item questionnaire to gather expert insights on the management of OA and OP in Indian settings. It explored various aspects, including epidemiology, risk factors, diagnostic practices, treatment preferences and challenges in current management. The collected data were analysed using descriptive statistics. Results: The study included 119 experts and nearly 75% of them identified knee OA as the most prevalent form of the condition. For the early management of OA, around 88% of respondents preferred a combination of nonsteroidal anti-inflammatory drugs (NSAIDs), physiotherapy, dietary modifications and exercise. Nearly 83% recognized family history, smoking, poor diet, advancing age and post-menopausal status as common risk factors for OP. Regarding screening practices, 55% of participants reported that blood tests, bone turnover markers and bone mineral density (BMD) assessments via ultrasound are the most commonly used methods. Around 77% believed that calcitriol supports fracture management, offers the benefit of weekly dosing for better compliance and is effective in treating OP. A majority (84.87%) of participants agreed that calcium aspartate is a well-tolerated and effective calcium supplement suitable for individuals across all age groups. Conclusions: This study indicates that knee OA is the most commonly observed form, with early management favouring NSAIDs, physiotherapy, dietary modifications and exercise. In OP, lack of awareness remains a key treatment gap, while calcium aspartate and calcitriol are widely regarded as effective and well-tolerated options.